2021
DOI: 10.2340/20030711-1000051
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-based health apps to promote physical activity during COVID-19 lockdowns

Abstract: Objective Periods of lockdown due to coronavirus disease 2019 (COVID-19) have a negative effect on individuals’ physical health and quality of life, and may result in a weakened immune response, leading to enhanced risk of infection. Due to lack of access to public resources during periods of lockdown many individuals cannot perform their usual daily physical activities. The aim of this short report is to discuss the use of mobile-based health applications and virtual reality systems for promoting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…And all those mHealth applications are enlisted that are used in the physical activity promotion at home. After observing these things, they concluded that mHealth applications could physically enhance health and be utilized during lockdown at home ( 34 ). Health and fitness apps mitigate the negative impact of the COVID-19 preventive measures on physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…And all those mHealth applications are enlisted that are used in the physical activity promotion at home. After observing these things, they concluded that mHealth applications could physically enhance health and be utilized during lockdown at home ( 34 ). Health and fitness apps mitigate the negative impact of the COVID-19 preventive measures on physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…In public health, digital sports through live streaming encourage people to stay active during the pandemic restrictions ( 7 , 42 , 43 ). Srivastav et al ( 34 ) published a report to discuss mHealth applications and VR systems for enhancing PA at home via a motivating and interactive digital environment. From WHO and the US Center for Disease Control and Prevention, the telehealth information was collected, and PA's data for the period of lockdown was also reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…If schools have the capacity, streaming exercise classes by the physical education teachers are recommended [3]. For all other age groups, online videos and mobile-based apps are recommended for the promotion of physical activity [103]. To further prevent physical inactivity and resulting physical and psychological consequences due to a lockdown, indoor and outdoor activities (e.g., aerobic exercise, strength, flexibilitystretching, and balance exercises) on the individual level are suggested [104][105][106][107].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…To facilitate the maintenance of a healthy lifestyle in the current non-face-to-face environment, the healthcare and wellness industries have made considerable advances in the development of e-health programs and in the field of wearable technologies designed to help users maintain healthy habits such as increasing their levels of physical activity [ 20 ], boosting their immune systems, and following balanced diets [ 21 ]. Hence, we suggest that governments and other stakeholders develop policies and programs that promote and support healthy lifestyles during both the pandemic response and recovery periods.…”
Section: Discussionmentioning
confidence: 99%